The erythropoietin‐derived peptide ARA 284 reduces tissue wasting and improves survival in a rat model of cancer cachexia. Issue 4 (18th May 2022) - Palus, Sandra; Elkina, Yulia; Braun, Tanja; von Haehling, Stephan; Döhner, Wolfram; Anker, Stefan D.; Cerami, Anthony; Brines, Michael; Springer, Jochen
Abstract: Background: Cancer cachexia (CC) is a severe complication during the last stages of the disease, which is characterized by the substantial loss of muscle and fat mass. Currently, there is no effective treatment of CC. Erythropoietin plays tissue‐protective role in different tissues. Based on the structure of erythropoietin, small non‐erythropoietic peptides were synthesized, which activate tissue‐protective signalling pathways. Methods: Here, we investigated the influence of the tissue‐protective peptide ARA 284 on CC in rats using the Yoshida hepatoma model. Results: Treatment with ARA 284 (1.7 μg/kg/day) counteracted the loss of body weight (12.46 ± 4.82% ARA 284 vs. 26.85 ± 0.88% placebo, P < 0.01), fat mass ( P < 0.01), and lean mass ( P < 0.01). It improved spontaneous activity of ARA 284‐treated animals. Further, gastrocnemius mass was increased (13.2% ARA 284 vs. placebo, P < 0.01) in association with induced p‐Akt ( P < 0.01) and decreased in p‐p38 MAPK, GSK‐3β, and myostatin (all P < 0.01), suggesting an induction of anabolic pathways. At the same time, we observed the significant increase in the survival of animals by high‐dose ARA 284 treatment (hazard ratio: 0.46, 95% confidence interval: 0.23–0.94, P = 0.0325). Conclusions: Taken together these results suggest that ARA 284 can be considered beneficial in experimental CC and it remains to be seen, if it can have similar beneficial effects in CC patient.